2022
DOI: 10.1590/s0004-2803.202202000-48
|View full text |Cite
|
Sign up to set email alerts
|

Cost Effectiveness of Using Terlipressin to Treat Hepatorenal Syndrome

Abstract: Background Hepatorenal syndrome (HRS) is the most severe form of acute kidney injury in patients with advanced cirrhosis, and it is associated with high mortality. It is usually diagnosed according to criteria defined by the International Ascites Club. Currently, the most frequently indicated pharmacological therapy for the treatment of HRS is a combination of splanchnic vasoconstrictors (terlipressin or norepinephrine) in combination with albumin. With the progressive increase in healthcare spending, it is i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…A meta-analysis study showed that the treatment strategy using terlipressin was more economical vs. noradrenaline from the perspectives of the Brazilian public health system and private health insurance [ 42 ]. Further, a cost-effectiveness study showed that terlipressin + albumin is cost-effective compared to norepinephrine + albumin administered to patients who were diagnosed with type 1 HRS in a controlled environment from a Brazilian public single-payer healthcare system [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis study showed that the treatment strategy using terlipressin was more economical vs. noradrenaline from the perspectives of the Brazilian public health system and private health insurance [ 42 ]. Further, a cost-effectiveness study showed that terlipressin + albumin is cost-effective compared to norepinephrine + albumin administered to patients who were diagnosed with type 1 HRS in a controlled environment from a Brazilian public single-payer healthcare system [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…13 A cost effectiveness analysis using data from a university medical center in Brazil determined that terlipressin in combination with albumin for the treatment of hepatorenal syndrome is cost-effective compared with norepinephrine in combination with albumin. 14 Limitations: The study was powered for several outcomes, but not for survival. Follow-up was limited to 90 days.…”
Section: |mentioning
confidence: 99%
“…Os especialistas sugerem que a resposta à terlipressina deve ser avaliada no dia 4, com Continuação, se a creatinina estiver inferior à linha de base, até que a creatinina seja ≤1,5 mg/dL por 48 horas ou por um total de 14 dias. Em pacientes que não respondem à terlipressina, deve-se considerar imediatamente o transplante de fígado (FERREIRA LM, et al, 2022).…”
Section: Prevenção E Manejo Da Condiçãounclassified